Maximum Tension Lines of MSE Embankments with Polymer and Metallic Reinforcements on Different Foundations Types a - Dennes T. Bergado; Salisa Chaiyaput; Ray M. Basilio; Ochakkraphat Sukchaisit; Takenori Hino (Lowland Technology International, 2021)
Four full scale and fully instrumented mechanically stabilized earth (MSE) test embankments were constructed to 6 m high for analyses and comparison of their behaviour, namely: one on hard ground, one on DCM improved ground and two on soft ground. The MSE on hard ground was reinforced with strong polymer geogrid in one side as well as metallic grids and strips in the other side. The MSE on improved ground was reinforced with hexagonal grids. Due to the negligible vertical and lateral movements in hard and improved ground, the consequent maximum tension lines were observed to closely follow the bilinear Coherent Gravity Method with standard distance from the facing of 0.3H where H is the equivalent height of the reinforced embankment. Moreover, two fully instrumented MSE were constructed on soft ground having similar trapezoidal cross-sections. One embankment was reinforced with polymer geogrids and the other with steel grids. The resulting large vertical and lateral movements of both embankments have almost identical patterns. The maximum tension lines of both embankments closely resemble to that of Coherent Gravity Method but with location of the vertical line portion at closer distances of 0.1H to 0.2H from the embankment facing.